ANALYSIS ON THE USE OF SMART CONTRACTS AND BLOCKCHAIN TO CREATE OFFICIAL DOCUMENTS IN BRAZIL - Amorin, Deivid Tiago; Malagolli, Guilherme Augusto (Revista Interface Tecnológica, 2022)
This article aims to compare the dynamics of the operation of an extrajudicial notary with a new model of making official documents proposing the use of technologies such as smart contracts and blockchain. The proposal to use smart contract technology comes with automation in the execution of clauses without the need for an intermediary and the judiciary to fulfill obligations. Blockchain, on the other hand, has the proposal to register, make it public, accessible anywhere in the world and make it impossible for the parties to change the contract. The motivation for carrying out the article was to develop a less bureaucratic, practical way, with less value and with the same legal certainty as an official document. These documents that in Brazil, despite all available technologies, continue for the most part with analogical and extremely bureaucratic production. For this, a bibliographic survey will be carried out on the blockchain and smart contracts. Continuing, a descriptive and analytical research will be carried out with employees of notaries in order to collect data for a comparison and analysis with the new proposed model.